The need to increase the innovative and investment activity of small businesses and entrepreneurs in the Republic of Uzbekistan - Gopparov M.O (Genius Journals, 2021)
The article discusses the theoretical issues of increasing the innovation and investment activity of small businesses in the transition to a digital economy and the content of key terms encountered in this process, the conditions created in our country, the main problems and proposals
Keywords: Action Strategy; Reform; Entrepreneurship; Small Business